Cacao (Theobroma cacao L.) Response to Water Stress: Physiological Characterization and Antioxidant Gene Expression Profiling in Commercial Clones - Osorio Zambrano, Mayra Andreina; Castillo, Darwin Alexander; Rodríguez Pérez, Loyla; Terán, Wilson (Frontiers in Plant Science, 2021)
The increase in events associated with drought constraints plant growth and crop performance. Cacao (Theobroma cacao L.) is sensitive to water deficit stress (DS), which limits productivity. The aim of this research was to characterize the response of seven (CCN51, FEAR5, ICS1, ICS60, ICS95, EET8 and TSH565) commercially important cacao clones to severe and temporal water deficit stress. Ten-month-old cacao trees were submitted to two treatments: well-watered and water-stressed until the leaf water potential (Ψleaf) reached values between -3.0 and -3.5 MPa. The effects of hydric stress on water relations, gas exchange, photochemical activity, membrane integrity and oxidative stress-related gene expression were evaluated. All clones showed decreases in Ψleaf, but TSH565 had a higher capacity to maintain water homeostasis in leaves. An initial response phase consisted of stomatal closure, a general mechanism to limit water loss: as a consequence, the photosynthetic rate dropped by approximately 98% on average. In some clones, the photosynthetic rate reached negative values at the maximum stress level, evidencing photorespiration and was confirmed by increased intracellular CO2. A second and photosynthetically limited phase was characterized by a drop in PSII quantum efficiency, which affected all clones. On average, all clones were able to recover after 4 days of rewatering. Water deficit triggered oxidative stress at the early phase, as evidenced by the upregulation of oxidative stress markers and genes encoding ROS scavenging enzymes. The effects of water deficit stress on energy metabolism were deduced given the upregulation of fermentative enzyme-coding genes. Altogether, our results suggest that the EET8 clone was the highest performing under water deficit while the ICS-60 clone was more susceptible to water stress. Importantly, the activation of the antioxidant system and PSII repair mechanism seem to play key roles in the observed differences in tolerance to water deficit stress among clones.